2018
DOI: 10.1186/s13071-018-3055-6
|View full text |Cite
|
Sign up to set email alerts
|

First cross-sectional, molecular epidemiological survey of Cryptosporidium, Giardia and Enterocytozoon in alpaca (Vicugna pacos) in Australia

Abstract: BackgroundEukaryotic pathogens, including Cryptosporidium, Giardia and Enterocytozoon, have been implicated in neonatal diarrhoea, leading to marked morbidity and mortality in the alpaca (Vicugna pacos) and llama (Lama glama) around the world. Australia has the largest population of alpacas outside of South America, but very little is known about these pathogens in alpaca populations in this country. Here, we undertook the first molecular epidemiological survey of Cryptosporidium, Giardia and Enterocytozoon in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…Three out of the five alpaca herds were positive, and the highest infection rate (42.9%, 15/35) was detected in animals from Qinghe (Table 1). The overall infection rate of E. bieneusi (15.1%) in this study was lower than that reported in alpacas in the highlands of Peru (51.6%) [3], and higher than that in Australia (9.9%) [4]. Currently, E. bieneusi has been isolated from humans, nonhuman primates, pigs, cattle, sheep, yaks, deer, cats and dogs, chickens, rodents, and snakes, as well as urban wastewater in China [18].…”
Section: Resultscontrasting
confidence: 76%
See 4 more Smart Citations
“…Three out of the five alpaca herds were positive, and the highest infection rate (42.9%, 15/35) was detected in animals from Qinghe (Table 1). The overall infection rate of E. bieneusi (15.1%) in this study was lower than that reported in alpacas in the highlands of Peru (51.6%) [3], and higher than that in Australia (9.9%) [4]. Currently, E. bieneusi has been isolated from humans, nonhuman primates, pigs, cattle, sheep, yaks, deer, cats and dogs, chickens, rodents, and snakes, as well as urban wastewater in China [18].…”
Section: Resultscontrasting
confidence: 76%
“…Among the three herds that were positive for E. bieneusi , genotype ALP3 ( n = 15) was detected in Qinghe, genotype ALP8 ( n = 1) in Hejing, and genotypes ALP3, ALP7, and P in Wensu (Table 1). Until now, molecular investigation of E. bieneusi in alpacas has been limited to two studies from farmed alpacas in Peru and Australia [3, 4], and two studies from captive alpacas in Chinese zoos [5, 6]. A total of 14 E. bieneusi genotypes (P, ALP1–8, Type IV, D, BEB6, J, and CHALTI) have been identified in alpacas worldwide [3–6], and genotype ALP1 was dominant in Peru and Australia [3, 4] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations